Произведение корней уравнения равно:

залина061 залина061    3   12.09.2019 14:30    0

Ответы
Полинаed Полинаed  07.10.2020 09:50
(x+1)(x+2)(x+3)(x+4)=3

Перемножаем скобки (x+1)(x+4) и (x+2)(x+3)
(x^2+5x+4)(x^2+5x+6)-3=0

Замена:
x^2+5x=t \\ \\ (t+4)(t+6)-3=0 \\ t^2+10t+24-3=0 \\ t^2+10t+21=0 \\ t_1+t_2=-10 \cup t_1t_2=21 \\ t_1=-3 \cup t_2=-7

Обратная замена:
1) \\ x^2+5x=-3 \\ x^2+5x+3=0 \\ x_1x_2=3 \\ \\ 2) \\ x^2+5x=-7 \\ x^2+5x+7=0 \\ D=25-28\ \textless \ 0

ответ: 3
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра